1971
DOI: 10.1111/j.1471-0528.1971.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Talc and Carcinoma of the Ovary and Cervix

Abstract: Summary An extraction‐replication technique was used to examine tissue from patients with ovarian and cervical tumours. In both conditions talc particles were found deeply embedded within the tumour tissue. The close association of talc to the asbestos group of minerals is of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…This banding is visible only on the electron translucent fibers. Some workers have called these bands decoration patterns in reference to similar diffraction contrast features observed on sheet silicates, especially talc (11). Diffraction contrast figures have been observed on all amphibole fiber types.…”
Section: Morphology Of Amphibole Asbestos Fibersmentioning
confidence: 98%
“…This banding is visible only on the electron translucent fibers. Some workers have called these bands decoration patterns in reference to similar diffraction contrast features observed on sheet silicates, especially talc (11). Diffraction contrast figures have been observed on all amphibole fiber types.…”
Section: Morphology Of Amphibole Asbestos Fibersmentioning
confidence: 98%
“…1 In animal studies, talc and other similar substances have been demonstrated to migrate from the vagina through the peritoneal cavity to the ovaries. 2 Henderson et al 3 also observed that particles with the appearance of talc were more prevalent in ovarian tumors than in normal ovarian tissue. Several epidemiologic studies have investigated perineal use of talcum powder as a potential risk factor for ovarian cancer and most have found elevations in risk, although there has been a large range in the risk estimates, from 1.1 to 3.9.…”
mentioning
confidence: 91%
“…Appraisal of the carcinogenicity of talc is important as it has been suggested that prolonged exposure to talc, with or without asbestos contamination, may be associated with malignant changes (Henderson et al, 1971;Merliss, 1971;Blejer and Arlon, 1973;Pelfrene and Shubik, 1975), and that fibrous particles with specific dimensions may be carcinogenic (Stanton and Wrench, 1972;Maroudas et al, 1973). Pott and Friedrichs (1972) In a study in hamsters (Smith et al, 1965;Smith, 1973) 25 mg of test dusts dispersed in 0-5 ml saline were administered intrapleurally to groups of 50 animals which were allowed to live their normal life spans.…”
Section: Cancer Studies In Animalsmentioning
confidence: 99%
“…Exposure to some mineral dusts in appropriate amounts can cause pneumoconiosis and in some instances can be associated with the development of cancer (Henderson et al, 1971;Murphy et al, 1971;British Medical Journal, 1973;Wagner et al, 1973). There is a possibility that talc alone or talc contaminated with asbestos may be associated with cancer formation (Merliss, 1971;Blejer and Arlon, 1973), although cancer has not so far been reported from its use therapeutically in the pleural cavity (Honma et al, 1963) or accidental introduction into the abdominal cavity from ruptured surgeons' gloves.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation